(untitled) (European Journal of Government and Economics, 2014)
This paper argues that an interest group’s networking skills in micro-states may be as important, if not more important than other variables discussed in the interest group influence literature. This argument is based on the recent literature on democratisation in micro-states which shows that politics in these states is personalistic in nature. The argument is supported by expert interviews undertaken in the Republic of Cyprus and the Turkish Republic of Northern Cyprus.